Carbapenem-resistant Klebsiella pneumoniae in ICU-admitted COVID-19 patients: Keep an eye on the ball. (December 2020) - Montrucchio, G.; Corcione, S.; Sales, G.; Curtoni, A.; De Rosa, F.G.; Brazzi, L.
Highlights: COVID-19 patient prognosis may be influenced by bacterial superinfection. Local epidemiology continues to play a role in bacterial superinfections. Critically-ill COVID-19 patients are more at risk of multidrug-resistant infections. Attention to carbapenemase-producing Klebsiella pneumoniae infections must remain high. Abstract: Here we report on seven intensive care unit (ICU) patients with coronavirus disease 2019 (COVID-19)-related acute respiratory distress syndrome (ARDS) who developed positive rectal swabs and invasive infections due to carbapenemase-producing Klebsiella pneumoniae (CP-Kp). Notwithstanding the infection prevention measures introduced during the COVID-19 pandemic and changes in the hospitalised population, attention to CP-Kp infections must remain high, especially in the critically ill setting.